32 + (129 - х : 8) : 4 = 64
(129 - х : 8) : 4 = 64 - 32
(129 - х : 8) : 4 = 32
129 - х : 8 = 32 · 4
129 - х : 8 = 128
х : 8 = 129 - 128
х : 8 = 1
х = 1 · 8
х = 8
Проверка:
32 + (129 - 8 : 8) : 4 = 64
32 + (129 - 1) : 4 = 64
32 + 128 : 4 = 64
32 + 32 = 64
64 = 64
32 + (129 - х : 8) : 4 = 64
(129 - х : 8) : 4 = 64 - 32
(129 - х : 8) : 4 = 32
129 - х : 8 = 32 · 4
129 - х : 8 = 128
х : 8 = 129 - 128
х : 8 = 1
х = 1 · 8
х = 8
Проверка:
32 + (129 - 8 : 8) : 4 = 64
32 + (129 - 1) : 4 = 64
32 + 128 : 4 = 64
32 + 32 = 64
64 = 64